Black carbon and other light‐absorbing particles in snow of central North America. Issue 22 (25th November 2014) - Doherty, Sarah J.; Dang, Cheng; Hegg, Dean A.; Zhang, Rudong; Warren, Stephen G.
Abstract: Vertical profiles of light‐absorbing particles in seasonal snow were sampled from 67 North American sites. Over 500 snow samples and 55 soil samples from these sites were optically analyzed for spectrally resolved visible light absorption. The optical measurements were used to estimate black carbon (BC) mixing ratios in snow ( C B C e s t ), contributions to absorption by BC and non‐BC particles, and the absorption Ångström exponent of particles in snow and local soil. Sites in Canada tended to have the lowest BC mixing ratios (typically 5–35 ng g −1 ), with somewhat higher C B C e s t in the Pacific Northwest (typically 5–40 ng g −1 ) and Intramountain Northwest (typically 10–50 ng g −1 ). The Northern U.S. Plains sites were the dirtiest, with C B C e s t typically 15–70 ng g −1 and multiple sample layers with >100 ng g −1 BC in snow. Snow water samples were also chemically analyzed for standard anions, selected carbohydrates, and various elements. The chemical and optical data were input to a Positive Matrix Factorization analysis of the sources of particulate light absorption. These were soil, biomass/biofuel burning, and fossil fuel pollution. Comparable analyses have been conducted for the Arctic and North China, providing a broad, internally consistent data set. As in North China, soil is a significant contributor to snow particulate light absorption in the Great Plains. We also examine the concentrations and sources of snow particulate light absorption across a latitudinal transect from the northern U.S. Great Plains to Arctic Canada by combining the current data with our earlier Arctic survey. Key Points: Light‐absorbing particles were measured at 67 central North American sites Sources of snow particulate absorption were soil, biomass burning, and pollution Great Plains snow in North America is cleaner than in the Great Plains of China